Studi Epistemologi Hukum Islam dalam Konteks Fatwa Majelis Ulama Indonesia - Firdaus, Syarif; Achmad, Mukhsin (LPPI Universitas Al-Qolam Malang, 2024)
This study aims to explore the epistemological foundations underlying the fatwa (religious decree) formulation processed by the Indonesian Council of Ulama (MUI) and analyze the dynamics of Islamic legal epistemology in the Indonesian context. Using a qualitative method with a content analysis and hermeneutical approach, this study examines MUI's fatwas published in the last decade, with contemporary Islamic epistemology theory and the maqashid sharia approach as the analytical framework. The research findings show that MUI applies an eclectic epistemological approach, integrating the bayani, burhani, and irfani methods in the fatwa establishment process. There is a significant effort to contextualize Islamic law with the realities of Indonesian society, reflected in the use of the principles of maslahah (public interest) and 'urf (local customs). MUI's collective ijtihad (independent reasoning) practice enriches the epistemological basis of the fatwas, but also poses challenges in synchronizing various perspectives. The novelty of this research lies in the comprehensive analysis of the dynamics of Islamic legal epistemology in MUI's fatwas in the digital era, which has not been widely explored before. This study reveals the flexibility and adaptability of Islamic legal epistemology in addressing contemporary issues, while also identifying the methodological challenges faced. The research recommends the development of a more systematic and transparent epistemological framework in the fatwa formulation process. Further studies are suggested to explore the impact of MUI's fatwas on Indonesia's socio-political dynamics and analyze the role of digital technology in the transformation of religious authority. Key words: epistemology; MUI, Islamic law; fatwa; legal